Vitamin D and Cancer - Trump, Donald L.; Johnson, Candace S.; SpringerLink (Online service) (New York, NY : Springer New York, 2011)
The following chapters provide excellent and comprehensive discussions of the potential role of vitamin D based therapies in breast, colorectal, prostate cancer and leukemia and myelodysplastic syndromes. These chapters also point out that the focus on these diseases is largely determined by the interests and expertise of the outstanding scientists who have chosen to pursue vitamin D based cancer therapeutics. To our knowledge, every tumor type ever evaluated has shown some biochemical and antiproliferative response to vitamin D. Similarly, vitamin D analogues, especially calcitriol, potentiate almost every cytotoxic agent with which combination therapies have been tested.
Keywords: Medicine; Oncology; Toxicology; Nutrition; Biomedicine; Cancer Research; Nutrition; Pharmacology/Toxicology.